Possible Consequences of the Replacement of Corporate Income Tax by Sales Tax - Sawulski , Jakub (Studia Oeconomica Posnaniensia, 2016)
Since 2008 a decline of share of Corporate Income Tax (CIT) revenues in GDP in Poland has been observed. Th e reasons for this are both the general dete- rioration in business conditions as well as the spread of tax avoidance. Some experts propose replacing it with a sales tax as a way of preventing lower CIT collection. Th e article presents the potential negative consequences of introducing such a form of taxation. At the same time the author presents reforms for improving CIT collection. Although he does not preclude despite the disadvantages demonstrated of introducing such a sales tax, such a proposal is worth considering.